Polyvinyl alcohol and amine-modified polyvinyl alcohol nanofiltration and reverse osmosis membranes - Bezuidenhout, Deon (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.